(untitled) (Homoeopathy for All, 2024)
Menopause is a natural biological transition in a woman’s life, often accompanied by a range of physical and psychological symptoms. The assessment tools under scrutiny encompass a wide array of questionnaires, surveys, and structured interviews designed to gauge psychological symptoms such as mood swings, depression, anxiety, and overall quality of life during the menopausal transition. The study aims to identify and analyze the effectiveness of these tools in accurately capturing the psychological aspects of menopause, with the ultimate goal of enhancing the quality of care and support provided to menopausal women.